1984
DOI: 10.1152/jappl.1984.57.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Muscle architecture and force-velocity relationships in humans

Abstract: The in vivo torque-velocity relationships of the knee extensors (KE), knee flexors (KF), ankle plantarflexors (PF), and ankle dorsiflexors (DF) were determined in 12 untrained subjects using an isokinetic testing device (Cybex II). These data were then matched to the predicted maximum forces and shortening velocities derived from muscle architectural determinations made on three hemipelvectomies (36). The torque-velocity curves of all muscle groups resembled that predicted by Hill's (19, 20) equation except at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
182
6

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(200 citation statements)
references
References 30 publications
(39 reference statements)
12
182
6
Order By: Relevance
“…However, when normalized to the optimal fibre length (i.e., in L 0 s −1 , with L 0 = 9.3 cm, Austin et al 2010), both maximal shortening velocities were similar (5.1 ± 2.2 and 6.2 ± 1.2 L 0 s −1 for VL and GM, respectively). The maximal shortening velocity of fascicle depends on the length of fascicle (here cancelled out by the normalization; Wickiewicz et al 1984) and the proportion of fast-twitch fibres (Barany 1967). Thus, considering the almost similar proportion of fast-twitch fibres in both muscles (Johnson et al 1973), our results are consistent.…”
Section: Estimation Of Maximal Knee Joint Velocity and Muscle Fasciclsupporting
confidence: 78%
“…However, when normalized to the optimal fibre length (i.e., in L 0 s −1 , with L 0 = 9.3 cm, Austin et al 2010), both maximal shortening velocities were similar (5.1 ± 2.2 and 6.2 ± 1.2 L 0 s −1 for VL and GM, respectively). The maximal shortening velocity of fascicle depends on the length of fascicle (here cancelled out by the normalization; Wickiewicz et al 1984) and the proportion of fast-twitch fibres (Barany 1967). Thus, considering the almost similar proportion of fast-twitch fibres in both muscles (Johnson et al 1973), our results are consistent.…”
Section: Estimation Of Maximal Knee Joint Velocity and Muscle Fasciclsupporting
confidence: 78%
“…Arrangement of PCSA and L f differed between the track sprinters and other cyclists, revealing a much larger PCSA but similar L f in the track sprinters. A long fascicle length (i.e., high numbers of sarcomeres in series) has theoretically been associated with high maximal muscle-fiber contraction velocity (63) and has been shown to relate to better sprint performance (14,15). PCSA is increased by muscle-fiber hypertrophy and is thought to result in proportional increases in maximal muscle force (27,64), assuming that specific force (F/ PCSA) remains constant.…”
Section: Physiology Of Sprinters: High Normalized Sprint Performance mentioning
confidence: 99%
“…As suggested by Edgerton et al (Wickiewicz et al 1983, Fukunaga et al 1996, CSA phys can be found from muscle volume, fibre length and fibre pennation angle. In the present calculations a muscle fibre length of 7 cm (Wickiewicz et al 1983(Wickiewicz et al , 1984 was used in combination with the muscle volumes and pennation angles obtained experimentally. Total muscle fibre force (F fibres ) was calculated from F quad /cos( p ), where quadriceps force (F quad ) was estimated from the measurement of maximal knee extension moment, assuming a 4.0 cm moment arm for the patella tendon (Wickiewicz et al 1984;Marshall et al 1990) and a ratio of patella tendon force to quadriceps tendon force of 0.70 at 70 deg knee flexion (Nisell et al 1989).…”
Section: Implications For Specific Muscle Tensionmentioning
confidence: 99%